Acceptance of a Claim for State Continuity: A Question of International Law and its Consequences - Ziemele, Ineta (Journal of the University of Latvia. Law, 2016)
This article provides an overview of the conflicting theoretical premises that characterize the debate and legal developments in international law in the fields of State succession and State continuity. It is argued that both identity and legal certainty principles have a role to play inthe modern understanding of State succession and State continuity. The article explains that the developments in international law and debate, especially those taking place within the so-called constitutionalist perspective on international law, provide for more support to the view taken by the Baltic states, when putting forward their claim to State continuity. The article argues that while international law does not determine the constitutional identity of a State, international law should be concerned with constitutional processes within the State since it is international law that attributes international consequences to these internal constitutional processes. The article sums up the most important legal issues regarding the claim to State continuity of Latvia.